Transformation of Plastic Waste into 3D Art as a Campaign Medium for Marine Ecosystem Degradation - Syamaidzar Dzakwan Abdi Qohar; Bangkit Sanjaya (Gorga : Jurnal Seni Rupa, 2026)
The global issue of plastic pollution in oceans has gained significant attention, particularly in Indonesia, which boasts the second-longest coastline worldwide and grapples with severe threats to its marine biodiversity. Consequently, this study endeavors to transform plastic waste into three-dimensional artworks as a campaign medium to address marine ecosystem degradation. The creative process is structured into three distinct stages: pre-creation, creation, and post-creation. Data analysis in this study employs descriptive qualitative analysis with an artistic reflection approach. This involves interpreting data derived from literature studies, observations, experiments, and documentation to comprehend the transformation of plastic waste into three-dimensional artworks and evaluate the alignment between the concept, visual representation, and the campaign message regarding marine ecosystem damage. The creation process yields two three-dimensional artworks that visually depict the suffering of marine biota due to plastic pollution through symbolic and critical visual approaches. The incorporation of octopus and orca whale figures as symbols reinforces the narrative of entrapment, vulnerability, and mortality of marine biota caused by human-generated plastic waste. In summary, these artworks not only possess aesthetic value but also serve as effective visual communication media for conveying social criticism and moral messages to the audience. Furthermore, they encourage societal awareness and behavioral change in reducing the consumption of single-use plastics, thereby contributing to the preservation of marine ecosystems’ sustainability.